Exclusively Included? Finland’s Inclusion Success Story and Hidden Dual System of Mainstream and Special Needs Education - Niemi Anna-Maija; Mietola Reetta (Springer, 2025)
This chapter focuses on the divide between special and mainstream education in the Finnish education system. We analyse how this divide runs through educational experiences, opportunities and pathways of students receiving special education. We first examine the different educational pathways opening up for different groups of students, and their experiences of educational choice-making. Then we move on to analyse pedagogical arrangements and practices across lower-secondary and upper-secondary levels; and to consider how different pedagogical practices expect and produce different kinds of students. Our analysis shows that distinct educational cultures make it challenging to move across the divide of special and mainstream education, and this divide contributes to students understanding of themselves as learners. The chapter draws on six studies conducted in recent decades in Finland, four different ethnographic studies, one life-history interview study and a longitudinal life-history study.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling